Estudio del proceso de lixiviación intensiva en los concentrados auríferos de la planta de tratamiento metalúrgico maquicer S.A. ubicada en el distrito minero San Gerardo cantón Camilo Ponce Enriquez Provincia del Azuay. - Villamahua Villamahua, Jhon Cristoforo (2015)
In this thesis Project, the main objective is improving the process for the benefit of the yielding gold. The efficiency, optimization and extraction was determined using the intensive leaching technique of the yielding gold generated in MAQUICER Metallurgical Company S.A. Referential Frame. Miming Geology of San Gerardo State, actually producing benefit Plant. Theoretical Framework: Generals knowledge of the gold, reduce operations of the size of the mineral particles, gravity concentration and cyanidation. Methodological Framework: description and analysis of samples of concentrated gravity, intensive cyanidation of the gravity concentration conventional cyanidation testing, analysis and establishment of results